The Horn of Africa : State Formation and Decay - Clapham, Christopher (London.: : Hurst & Company, 2017)
Why is the Horn such a distinctive part of Africa? This book, by one of the foremost scholars of the region, traces this question through its exceptional history and also probes the wildly divergent fates of the Horn's contemporary nation-states, despite the striking regional particularity inherited from the colonial past. Christopher Clapham explores how the Horn's peculiar topography gave rise to the Ethiopian empire, the sole African state not only to survive European colonialism, but also to participate in a colonial enterprise of its own. Its impact on its neighbours, present-day Djibouti, Eritrea, Somalia and Somaliland, created a region very different from that of post-colonial Africa. This dynamic has become all the more distinct since 1991, when Eritrea and Somaliland emerged from the break-up of both Ethiopia and Somalia. Yet this evolution has produced highly varied outcomes in the region's constituent countries, from state collapse (and deeply flawed reconstruction) in Somalia, through militarised isolation in Eritrea, to a still fragile 'developmental state' in Ethiopia. The tensions implicit in the process of state formation now drive the relationships between the once historically close nations of the Horn.
Acknowledgements -- List of Acronyms and Indigenous Words -- Maps -- Introduction: An African Anomaly -- 1. The Power of Landscape -- 2. Histories of State Creation and Collapse -- 3. State Reconstruction in Ethiopia -- 4. Eritrea: The Tragedy of the Post-Insurgent State -- 5. Managing Somali States -- 6. The Horn, the Continent and the World -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 205-212) and index.
Keywords: Since 1900; Politics and government..; Horn of Africa -- History -- 20th century; Horn of Africa -- History -- 21st century; Horn of Africa -- Politics and government -- 20th century; Horn of Africa -- Politics and government -- 21st century; Ethiopia -- Politics and government -- 1974-1991.; Ethiopia -- Politics and government -- 1991-; Africa -- Horn of Africa..; Ethiopia..; History..